MODEL PENGAWASAN PRESTASI KERJA PEGAWAI DI RUMAH SAKIT ARIFIN NU’MANG RAPPANG - Hendrika Utami; Erfina Erfina; Andi Astinah Adnan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
This study aims to determine the supervision model at Arifin Nu’mang Rappang Hospital, to determine the effect of the supervision model on employee work performance at Arifin Nu’mang Rappang Hospital, and to determine the factors that influence supervision at Arifin Nu’mang Rappang Hospital.The research method approach that will be used in this research is a quantitative descriptive approach. The population in this study were medical employees at Arifin Nu’mang Rappang Hospital wich consisted of 176 employees. The sample technique used is Purposive Sampling using the Slovin formula to produce 64 samples. Data collection techniques performed in this study were observation, interviews, questionnaires, and literature studies. The collected data is then processed and analyzed using quantitative descriptive analysis techniques with the help of descriptive statistics using SPSS 21.0 and Likert Scale. The results showed that the supervision model at Arifin Nu’mang Rappang Hospital was in the rare category with a percentage of 53.95%, the influence of the supervisory model on the work performance of employees at Arifin Nu’mang Rappang Hospital with a percentage of 55% influence, the factors affecting influencing supervision in Arifin Nu’mang Rappang Hospital is in the rare category with a percentage of 51,36%.